Singapore : Detailed Assessment of Observance-Assessment of Observance of the CPSS-IOSCO Principles for Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the Detailed Assessment of Observance of the Committee on Payment and Settlement Systems-International Organization of Securities Commissions Principles for Financial Market Infrastructures(FMIs) in Singapore. Singapore has a well-developed payment, clearing, and settlement infrastructure, which includes two central counterparties for financial products. The infrastructure includes a large value payment system operated by the central bank and securities and derivatives clearing and settlement systems operated by the Singapore Exchange Limited. The FMIs in Singapore are subject to effective regulation, supervision, and oversight of the Monetary Authority Singapore (MAS). The legal framework provides the MAS with sufficient powers to obtain timely information and induce change.